Communicating Identity in LinkedIn From Indonesian Cultural Perspective - Nicholas Jonathan Hendrik Wibowo (k@ta: A Biannual Publication on the Study of Languange and Literature, 2019)
This paper examines how Indonesians communicate identities in LinkedIn as means of personal branding from Indonesian culture. The study was conducted using descriptive qualitative approach with textual analysis focusing on LinkedIn profiles. The analysis involved some notions: positive ethos in LinkedIn, and Indonesian culture social order to unveil the motivations in making profiles in such ways. From the findings, the participants sought to be regarded as professionals in work, and sought positive values as hierarchy remains crucial in Indonesia. The participants wanted high positions in that hierarchy to stand out and given a priority in job-seeking context. Hence, they made their profiles using English language, made a detailed description, and provide self-portraits wearing suits. They also mentioned the name of their alma mater and positions in present work. People planning to take part in the job market best serve their interests by becoming familiar with LinkedIn.